2016
DOI: 10.3389/fmicb.2016.00324
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Consortium with High Cellulolytic Activity (MCHCA) for Enhanced Biogas Production

Abstract: The use of lignocellulosic biomass as a substrate in agricultural biogas plants is very popular and yields good results. However, the efficiency of anaerobic digestion, and thus biogas production, is not always satisfactory due to the slow or incomplete degradation (hydrolysis) of plant matter. To enhance the solubilization of the lignocellulosic biomass various physical, chemical and biological pretreatment methods are used. The aim of this study was to select and characterize cellulose-degrading bacteria, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 43 publications
(29 reference statements)
3
32
0
2
Order By: Relevance
“…Daily bioaugmentation also proved more effective than a one-time application as a washout in a continuous reaction with short HRT quickly decreases the positive impact [63]. Similar results of 15% higher sCOD and an increase of 38% in biogas yield with bioaugmentation of a selected microbial consortia with high cellulolytic activity in a batch digestion of maize silage were published [64]. On the contrary, bioaugmentation with the fungus Piromyces rhizinflata to the hydrolysis stage did not improve digestion significantly [65].…”
Section: Combined Pretreatmentmentioning
confidence: 53%
“…Daily bioaugmentation also proved more effective than a one-time application as a washout in a continuous reaction with short HRT quickly decreases the positive impact [63]. Similar results of 15% higher sCOD and an increase of 38% in biogas yield with bioaugmentation of a selected microbial consortia with high cellulolytic activity in a batch digestion of maize silage were published [64]. On the contrary, bioaugmentation with the fungus Piromyces rhizinflata to the hydrolysis stage did not improve digestion significantly [65].…”
Section: Combined Pretreatmentmentioning
confidence: 53%
“…In order to increase the methanogenesis efficiency and the methane content in the produced biogas, researchers often introduce some additional cells into the methane tank besides the anaerobic sludge. These microorganisms usually stimulate the processes at various stages of the cellulose-containing substrates' conversion into methane: hydrolysis of complex substrates [1,2,37], additional formation of hydrogen [38] and methane [39].…”
Section: Introductionmentioning
confidence: 99%
“…and Fibrobacteraceae sp, the efficiency of biogas production from rice straw in anaerobic digester was increased by 9.3% when using the optimized operational condition [8]. Similarly, using a mesophilic microbial consortium consisting of 3 genera of bacteria, including Bacillus, Providencia, and Ochrobactrum, to decompose maize silage at 30°C and 37°C, it was found that the biogas production was increased by 38% [9]. Subcultivation and enrichment of microbial consortium obtained from swine manure were demonstrated to improve the biogas yield up to 40% produced from anaerobic digestion of lignocellulose [10].…”
Section: Introductionmentioning
confidence: 93%